THE IMPORTANCE OF THE CERVICAL CANCER ORGANISED SCREENING PROGRAMS - Nikčević Kovačević, Ivana (Medicinski podmladak, 2024)
According to the most recent published data from 2020, cervical cancer is among the first five most frequently diagnosed cancers in the female population. It is the second leading cause of cancer mortality in young, working women during their reproductive period. Prevention of cervical cancer through screening programs has been applied since the 1960s, and the scientific community agrees that it is a highly preventable disease with a strong possibility for cure if detected in a premalignant and early malignant phase and effective treatment administrated without delay. Countries that effectively implement organized screening programs record a significant decrease in the incidence and mortality rates of cervical cancer. Their experience can be useful as a model for countries that still do not have established organized programs or have an unsatisfactory level of implementation or quality. These are mainly underdeveloped and developing countries, where exposure to risk factors is still very high, preventive activities are limited and consequently, the burden of cervical cancer is still at a very high level. The challenge remains how to adapt screening program strategies to the conditions of those countries to achieve high coverage of the target population with a test of appropriate performance to establish control over the increasing trend and in the coming decades to reach the targeted decline in incidence and mortality rates. So far, it is the only malignant disease for which there is scientific evidence that it can be eliminated to a frequency that will no longer represent a public health problem. Reducing the incidence rates should be an effect that would be seen at the global level, and to achieve it, it is necessary to strongly support countries in establishing adequate programs of prevention and early detection of cancer supported by effective treatment and care.